2019
DOI: 10.1016/j.sapharm.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing state-mandated training requirements for naloxone-dispensing pharmacists

Abstract: A lack of standardized naloxone training requirements for naloxone-dispensing pharmacists may affect the rate of adoption of enhanced pharmacy naloxone dispensing practices at community pharmacies and suboptimal education of patients at risk of opioid overdose. Ensuring pharmacists' preparedness to serve as naloxone providers is necessary to meaningfully prevent opioid overdose deaths in their communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
(10 reference statements)
0
28
0
Order By: Relevance
“…29,59,60 All 50 states had implemented enhanced pharmacy naloxone access laws by 2018, and 19 states required naloxone education for pharmacists engaged in naloxone dispensing or prescribing. 47 The standing orders issued by most states allow pharmacists to dispense naloxone via protocol without a written order from a physician, which makes it possible for pharmacists to screen patients at risk of overdose, dispense naloxone, and educate individuals about using naloxone. Despite the standing orders, a widespread issue of pharmacists not stocking naloxone is reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,59,60 All 50 states had implemented enhanced pharmacy naloxone access laws by 2018, and 19 states required naloxone education for pharmacists engaged in naloxone dispensing or prescribing. 47 The standing orders issued by most states allow pharmacists to dispense naloxone via protocol without a written order from a physician, which makes it possible for pharmacists to screen patients at risk of overdose, dispense naloxone, and educate individuals about using naloxone. Despite the standing orders, a widespread issue of pharmacists not stocking naloxone is reported.…”
Section: Discussionmentioning
confidence: 99%
“…45,[47][48][49][50] State-mandated training requirements were reviewed for pharmacists dispensing naloxone in states where the legislatures permitted enhanced access to naloxone through pharmacies. 47 To date, all states except Nebraska have enhanced pharmacy naloxone access laws, including 43 states with standing orders and 14 state with protocol orders. 15,51 However, only 19 states require naloxone training or education programs for pharmacists.…”
Section: Programs For Practicing Pharmacistsmentioning
confidence: 99%
“…In these secret shopper studies, investigators evaluated the availability of naloxone from pharmacies in California and Texas, 2 of the 50 states that in recent years have passed legislation to empower pharmacists to dispense this life-saving medication without a direct physician’s prescription. (11) 8 As Evoy et al report (4), in 4 pharmacy chains, pharmacists in Texas, in which standing orders allow pharmacists to dispense naloxone, 83.7% of 2127 pharmacies contacted would dispense naloxone without an outside prescription; 69.4% would dispense naloxone and had it in stock. Puzantian et al report (5) that in a random sample of all pharmacies in California, which allows pharmacists to furnish the drug without a physician’s prescription, 23.5% of 1147 pharmacies that were contacted and provided data indicated that naloxone was available and could be provided without a prescription.…”
mentioning
confidence: 99%
“…Other actionable reasons may account for the limitations in availability in both states, including the training and comfort level of pharmacists, awareness of the legislation, and insurance coverage. (11) Improved training of pharmacists may be needed to make naloxone universally available for the prevention of opioid-related deaths. Such efforts will require resources, investment, and organizational supports.…”
mentioning
confidence: 99%
“…A retail-dispensed prescription data analysis between 2007 and 2016 found an average increase of 79% of naloxone dispensed in U.S. retail pharmacies in states where the new naloxone access laws have been passed versus states that have not passed similar naloxone access legislation (1). Since November 22, 2017, all 50 states have now implemented a naloxone pharmacy access law, but only 19 states require pharmacists to have focused naloxone training prior to participation in the prescribing and dispensing of naloxone(2).…”
mentioning
confidence: 99%